Postkolonialna koncepcja hybrydyczności a prawa własności kulturowej. Pomiędzy dynamiką kultury a esencjalizmem - Sulikowski, Adam; Wojtanowski, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article deals with the concept of “hybridity” in the context of cultural property rights. Authors, who embrace an anthropological approach, argue that there is tension between the existence of cultural hybrids and theoretical foundations embedding the above-mentioned field of law. As a matter of fact, cultural property — as well as cultural heritage, its subsequent extension — presupposes an alignment between a particular culture and an appropriate group. Accordingly, culture should unproblematically belong to specified “owners” who have the right to control it. However, this premise is particularly troublesome in the context of cultural hybrids as an attempt to specify “holders” of such products seems to be beleaguered. Additionally, the paper contends that the concept of cultural property itself distorts culture — it portrays its subject as a static, uncontaminated and easily determinable phenomenon. Furthermore, authors show that cultural property contributes to false perceptions of indigenous people in postcolonial contexts. In general terms, the article demonstrates the prolific character of postcolonial reflection in the context of the law.
Keywords: kultura; własność; hybryda; postkolonializm